Modelling and forecasting tourism demand in Portugal: past, present and future - Daniel, Ana C. M. (2007)
A literature survey shows that considerable attention has been given to tourism demand forecasting.However, in Portugal only the Direcção Geral do Turismo (General Tourism Board), Investimentos, Comércio e Turismo de Portugal (Investments, Commerce and Tourism for Portugal), and academic researchers have carried out some work on tourism demand modelling and forecasting. Research on recent developments and methodologies for modelling and forecasting tourism in Portugal is still quite limited. Hence, the main purpose of this paper is to surveythe empirical research available to date for Portugal and provide suggestions for future studies.